2016
DOI: 10.1063/1.4966254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the temporal variations of plasma composition on the cyclic formation of dust in hexamethyldisiloxane-argon radiofrequency discharges: Analysis by time-resolved mass spectrometry

Abstract: Cyclic formation of dust nanoparticles in hexamethyldisiloxane (HMDSO, Si2O(CH3)6)-argon RF discharge with pulsed injection of HMDSO was studied using time-resolved mass spectrometry (MS) and optical emission spectroscopy (OES). A large amount of C2H2, considered as promoter of dust nucleation in hydrocarbon plasmas, was found as a by-product of HMDSO fragmentation. Although no negative ions were detected the presence of C2H2 in the HMDSO-Ar discharge supports the hypothesis of a dust growth mechanism based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 38 publications
6
35
0
Order By: Relevance
“…The maximum and following decrease of ν quenching occurs when dust starts to grow in the plasma. HMDSO and its plasma-generated compounds see their density decrease with dust formation and growth, as previously reported through plasma sampling mass spectrometry measurements [23]. Smaller fragments, resulting from the C 2 H 2 dissociation, are not efficient for quenching argon metastable atoms [60].…”
Section: Evolution Of Dusty Plasma At Multi-scale In the Frequency Dosupporting
confidence: 68%
See 2 more Smart Citations
“…The maximum and following decrease of ν quenching occurs when dust starts to grow in the plasma. HMDSO and its plasma-generated compounds see their density decrease with dust formation and growth, as previously reported through plasma sampling mass spectrometry measurements [23]. Smaller fragments, resulting from the C 2 H 2 dissociation, are not efficient for quenching argon metastable atoms [60].…”
Section: Evolution Of Dusty Plasma At Multi-scale In the Frequency Dosupporting
confidence: 68%
“…The cyclic phenomena presented above have already been observed for the same Ar/HMDSO dusty plasma [22,23,48], and its response was analysed in the mHz frequency domain using TRG-OES coupled with a collisionalradiative model [48,51]. It was shown that both the electron temperature and density have cyclic behaviour, with a frequency corresponding to the dust formation/disappearance cycle.…”
Section: Dynamical Processes In Rf Dusty Plasma: Multi-scale Approachmentioning
confidence: 76%
See 1 more Smart Citation
“…Though judicious control of the operating conditions, it was however found that pulsing the injection of HMDSO can lead to the formation of successive generations of nanoparticles, or dust, in the gas phase . A recent PSMS study in such conditions showed that acetylene (C 2 H 2 ) is formed as a result of HMDSO fragmentation in Ar/HMDSO plasmas and may be considered as the main origin of dust formation in analogy with hydrocarbon dusty plasmas. Acetylene‐based dusty plasmas have been extensively studied, proving that C 2 H 2 is a strong dust promoter via the confinement of the C 2 H − ion.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nonthermally reactive atmospheric pressure plasma has attracted much attention as a dry method of film deposition for its simplicity and versatility . The plasma is composed of charged particles and excited neutral precursors with high reactive energies . It can provide a unique environment for chemical reactions and film growth, which is distinct from typical condensed chemical reactions driven by a single heat source.…”
Section: Introductionmentioning
confidence: 99%